PENDIDIKAN KELUARGA DALAM PERSPEKTIF HUKUM ISLAM (STUDI KASUS WANITA KARIR) - Thobroni, Ahmad (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2019)
ABSTRACTAlong with the times, women today, especially those left in big cities tend to play a double roles. Some of them even have multifunctionally function because they have got the widest opportunity to develop themselves. Thus work and important positions in society are no longer monopolized by men. They work in various sectors with a variety of different reasons. Not infrequently they must increase competitiveness and deal with men. These are what are usually referred to as career women.The reason of women leaving home to work include (1) filling in their spare time (2) helping to increase the cost of family needs (3) providing for the family (4) as a result of the needs of the industrial sector that requires female labor, and so on.The position of career women who work outside the home often raises new problems. Their responsibilities as housewives are potentially neglected. The Islamic concept that places mothers as the first â€œmadrasahâ€ for children's education often cannot be run optimally. In addressing the issue of women who work there are 2 (two) opinions among scholars. First, rejecting women for careers, by working outside the hause there will be many obligations that must be abandoned. Second, allowing women to have a career with the demands of basic needs that require them to work. The woman's energy is needed by the community and the work cannot be done by men. Regarding the first opinion, women may work outside but their obligations as mothers and educators for their children must still be fulfilled.Â Keywords: Family Education, Islamic Law, Career Women